Optimal synthesis of trigeneration systems subject to environmental constraints - Carvalho, Monica; Serra, Luis Maria; Lozano, Miguel Angel (Energy (Oxford), 2011)
Environmental information obtained through Life Cycle Analysis techniques has been incorporated into a Mixed Integer Linear Programming (MILP). The solution of the model provides the optimal configuration and operation of an energy supply system to be installed, minimizing the environmental burden associated with production of equipment and consumption of resources. Starting from a superstructure of cogeneration system with additional components highly interconnected, the energy supply system was optimized considering specific demands of a hospital located in Zaragoza, Spain. The objective functions took into account the kilograms of CO 2 released and Eco-indicator 99 Single Score. Also considered were price of energy resources, price and amortization possibilities of the equipment and options for selling surplus electricity to the electric grid. The effect of electricity generation conditions on the optimal configuration was examined by varying the source of electricity production in Spain and considering natural gas/electricity mixes from alternate countries. The ratio between local electricity emissions and natural gas emissions ( α factor) was found to have the highest impact on the configuration of the system. Therefore the α factor could be considered the strongest influencing factor when deciding the optimal configuration of a system that minimizes environmental loads.